(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
A scheelite concentrate, containing 32% WO3, obtained from an indigenous tungsten ore of Chitral, NWFP, Pakistan, has been beneficiated by froth flotation technique to produce high quality tungsten concentrate assaying 64.8% WO3 with 84.47% recovery. This paper presents results on the optimization of flotation parameters like pH, pulp density and reagents. The optimum grade and recovery have been obtained at a feed size of 80 % passing 74 μm, pulp pH of 10.5, pulp solids 25%, oleic acid 0.30 kg/t, polyglycol 0.02 kg/t and sodium silicate 0.125 kg/t of the feed. The obtained tungsten concentrate meets the specifications required to produce tungsten metal and tungsten based chemicals. Key words: Scheelite Concentrate; Beneficiation; Flotation; Grade; Recovery DOI: http://dx.doi.org/10.3329/bjsir.v46i1.8115 Bangladesh J. Sci. Ind. Res. 46(1), 123-126, 2011